Airport Perimeter Security System Readiness Analysis (Case Study At Budiarto Curug-Tangerang Airport) - Sugih Arti, Endang; Praptiningsih, Nunuk; Ari Widagdo, Rinosa; Wagini, Dini (Siber Journal of Transportation and Logistics, 2023)
This study aims to determine how the perimeter conditions and solutions to the obstacles that exist in the Budiarto Airport Management Unit (UPBU). The study used a descriptive method and data collection used was the method of interviewing, observing and documenting. The data analysis technique used is data reduction, data display, and conclusing drawing. This study used several respondents as a sample, one airport security officer and four village/sub-district officials in four villages surrounding the Budiarto Airport Management Unit (UPBU). This research shows that the perimeter security system at Budiarto Airport is still not ready and tight, because avsec (aviation security) is only located or standing guard at the gate only, the results of interviews with the surrounding village chief also showed that there are still many residents who are still approaching the airport security area because they still do not understand the meaning of warning signs on the perimeter.